The formation of the professional competence of the future elementary school teacher by the facilities of innovative pedagogical techniques (Pedagogy of Higher and Secondary Education, 2013)
Zychkov A. К. The formation of the professional competence of the future elementary school teacher by the facilities of innovative pedagogical techniques.In the article the problems of the professional competence as a component of the innovative activity of the future elementary school teacher are discussed.
Keywords: competence; competency; pedagogical technology; innovative techniques